Aspek Susila Dalam Akun Facebook Bupati Klungkung I Nyoman Suwirta - IMBA Purnomo; Yudha Pramiswara; RH Wasisto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Problems on social media are increasingly complex and worrying. Problems that occur starting from insults, defamation, harsh words and also that get the most attention are hoaxes. The various problems seem to give the impression that social media cannot provide a portion of moral or moral learning that can be learned by users (netizens). Moreover, currently there are many cases that lead to legal trials affecting various groups in the country for violating Law No. 11 of 2008 concerning Information and Electronic Transactions (ITE). In the midst of the nation's improved condition after the post-presidential election, unfortunately there are still many discussions in social media groups that present hoax news, harsh words and blasphemous / hate speech which is of course very dangerous and not educating at all. Therefore, this study was conducted to provide information on the moral aspects of the Klungkung Regent's Facebook account, I Nyoman Suwirta. The object of research is the expression and status that contains moral or moral values. The object used as an example is the comment that contain positive connotations. Meanwhile, the analysis used is the dressing and paraphrasing techniques. Furthermore, the presentation of the results of the analysis is done by informal methods, namely by the description of ordinary words. The results showed that the moral aspects of the Facebook account I Nyoman Suwirta are praise, care, positive innovation, pattern, constructive criticism